Blockchain Authentication Methods and Hadith Authentication Methods (Comparative Study) - Akram Akram; Saiful Anwar (Riviera Publishing, 2025)
Blockchain is a distribution system consisting of a set of blocks connected to each other using cryptographic technology. Each block consists of a set of information that is recorded in a decentralized manner and does not rely on one party to validate the transaction. Each block stores a reference to the previous block in the Block Chain network, any modifications or changes in one block will be immediately known because the changes are not contained in other blocks, this property is meant by distributed, known as DLT (Distributed Ledger Technology). The blockchain authentication method is a series of processes used to verify the validity of a transaction or information stored in the blockchain network. Similar to the blockchain, the hadith as the second source of law after the Qur'an, when conveyed by the Prophet Muhammad Saw to the companions (sahabah), the companion then distributed it to other companions not only the matan (the content of the hadith) but also the sanad (narrators). The authenticity of the hadith is maintained by the composition of the chain of narrators called sanad and the figure of the narrator who has the capability and is trusted to convey a hadith. This method is then known as decentralized and distributed information, which is the same information owned by many parties, so it is very difficult to make changes unless it changes all parties who receive the information (mutawatir). This research will compare the concepts of blockchain authentication methods and hadith authentication methods with a literature review approach.